2004
DOI: 10.1002/hlca.200490115
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Structures of Lutein and Zeaxanthin

Abstract: A series of new esters of lutein (1a) have been prepared with the aim of confirming the structure of lutein via an X-ray crystal-structure analysis. Although well crystallized, only one of the derivatives, the (À)-(1R)-menthyl carbonate (1i) proved to be useful for a complete structure analysis. The same derivative of zeaxanthin (2a) also allowed its crystal structure to be determined. Both analyses represent the first successful X-ray crystal structure analyses of the most important xanthophylls. At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…We also report the room-temperature crystal structure of canthaxanthin, to compare directly with the Bart & MacGillavry (1968) room-temperature structure. The crystal structure of the bis[menthyl carbonate] derivative of RR-zeaxanthin has been reported previously (Linden et al, 2004), but to our knowledge the crystal structure of RS-zeaxanthin reported here is the first crystal structure of a free zeaxanthin. We will show that important variations of the various proposed colourtuning parameters have been achieved in a field where it was previously regarded as notoriously difficult to produce crystals.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…We also report the room-temperature crystal structure of canthaxanthin, to compare directly with the Bart & MacGillavry (1968) room-temperature structure. The crystal structure of the bis[menthyl carbonate] derivative of RR-zeaxanthin has been reported previously (Linden et al, 2004), but to our knowledge the crystal structure of RS-zeaxanthin reported here is the first crystal structure of a free zeaxanthin. We will show that important variations of the various proposed colourtuning parameters have been achieved in a field where it was previously regarded as notoriously difficult to produce crystals.…”
Section: Introductionmentioning
confidence: 60%
“…Corresponding bond lengths and angles for RS-zeaxanthin, in general, also agree closely with those found for AXT and canthaxanthin. One difference is the C4-C5 bond length which is 1.513 (3) Å for RS-zeaxanthin, but ranges from 1.457 (4) to 1.480 (4) Å for the other five structures; however, the C4-C5 bond length in RS-zeaxanthin is similar to that in -carotene, which is 1.500 (7) Å (CSD entry CARTEN2; Allen, 2002) and the bis[menthyl carbonate] derivative of RRzeaxanthin (Linden et al, 2004) at 1.519 (7) and 1.512 (6) Å . This arises from the presence of the keto oxygen at the 4position in the AXT and canthaxanthin molecules, which leads to a shortening of the C4-C5 bond due to conjugation with the C5-C6 double bond.…”
Section: Comparison Of the Carotenoid Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The latest published structures for lutein and zeaxanthin, based on crystallographic data, are given in [41], and for canthaxanthin in [42]. [41] (latest published) and canthaxanthin [42].…”
Section: Macula Lutea Pigmentsmentioning
confidence: 99%
“…Interestingly, all the effects were observed at much lower concentrations of the pigment in the lipid phase (below 1 mol%; in some cases as low as 0.05 mol%) than those of other xanthophylls such as lutein or zeaxanthin (for review on other carotenoids see: Gruszecki & Strzałka, 2005). This can be the consequence of different structures of these macular carotenoids themselves (Bart & MacGillavry, 1968;Linden et al, 2004). Apart from the functional keto-group in the ionone ring of canthaxanthin, the shape of the polyene chains in these xanthophylls differ to such an extent that this can affect their binding to the lipid membrane and the formation of molecular aggregates of xanthophyll molecules.…”
Section: Overview Of the Experimental Datamentioning
confidence: 99%